2002
DOI: 10.1177/107327480200900502
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics of Head and Neck Cancer

Abstract: Head and neck cancers comprise a complex genetic disease. Although much has been learned about the molecular genetics of head and neck cancers, continued study of multiple genes is critical for further progress. Gene therapy, although promising, must also overcome this complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0
20

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 85 publications
7
48
0
20
Order By: Relevance
“…[24][25][26][27][28] However, some previous reports did not find any prognostic significance of p53 in head and neck cancers. 29 Recently, Balz et al 30 reported that 95% of the head and neck cancers lack normal p53 function and concluded that inactivation of p53 per se is not a suitable choice as a prognostic or predictive marker. Since prognosis has a multifactorial molecular background, it is important to look for a battery of markers for its influence on the prognosis of the patients in a larger cohort.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28] However, some previous reports did not find any prognostic significance of p53 in head and neck cancers. 29 Recently, Balz et al 30 reported that 95% of the head and neck cancers lack normal p53 function and concluded that inactivation of p53 per se is not a suitable choice as a prognostic or predictive marker. Since prognosis has a multifactorial molecular background, it is important to look for a battery of markers for its influence on the prognosis of the patients in a larger cohort.…”
Section: Discussionmentioning
confidence: 99%
“…CCND1'in aktivitesi G1 fazı süresince maksimum seviyede kalır ve p16, p21 ve p27 gibi tümör baskılayıcı genler tarafın-dan inhibe edilebilir. 5 Meme, baş-boyun, özofagus, larinks ve akciğer gibi çeşitli kanserlerde CCND1 aktivasyonu ya da aşırı ekspresyonunun gözlen-mesi CCND1'deki değişikliklerin karsinogenezde rol oynadığını düşündürmektedir. 6,7 Yapılan çalış-malarda HNC'de, tümörlerin %18-%58'inde CCND1 amplifikasyonu gözlenmiş, 8,9 genin amplifikasyonu ya da aşırı ekspresyonu, nüks, nodal metastaz ve ölümle ilişkilendirilmiştir.…”
Section: Baş-boyun Kanserli Hastalarda Siklin D1unclassified
“…Approximately 80-90% of cases of HNSCC are attributed to prolonged tobacco and/or alcohol use (2). However, only a small fraction of those who consume tobacco or alcohol develop this disease, suggesting that genetic factors are also important in its pathogenesis (4)(5)(6). Fundamental to the genetic basis of all cancers is the overexpression of oncogenes and/or silencing of tumor suppressor genes.…”
Section: Introductionmentioning
confidence: 99%